Term induction of labor and subsequent preterm birth - LEVINE, Lisa D. (2013)
OBJECTIVE: Although the rate of inductions continues to rise, there is a paucity of data investigating subsequent pregnancy outcomes after induction. Our objective was to compare term inductions to term spontaneous labor and evaluate the rate of subsequent spontaneous preterm birth (sPTB). STUDY DESIGN: A retrospective cohort study of women with 2 consecutive deliveries from 2005–2010 was performed. Term inductions or term spontaneous labor in the index pregnancy were included, and those with a prior sPTB were excluded. Data were obtained through chart abstraction. The primary outcome was sPTB (<37wks) in a subsequent pregnancy. Categorical variables were compared with χ(2) analyses and logistic regression was used to calculate odds. RESULTS: 887 women were included (622 inductions, 265 spontaneous labor). The overall subsequent sPTB rate was 7.2%. Term inductions were less likely to have a subsequent sPTB compared to term spontaneous labor (6 vs. 11%; OR 0.49, 95% CI 0.29–0.81, p=0.005). This remained after adjusting for confounders (aOR 0.55, p=0.04). The sPTB risk depended on gestational age of index delivery. At 37–38.9wks, the sPTB rate after spontaneous labor was 24% vs. 9% after induction (OR 3.0, 95% CI 1.44–6.16, p=0.003). This was not significant for 39–39.9wks (p=0.2) or ≥40wks (p=0.8). CONCLUSIONS: Induction is not a risk factor for subsequent sPTB. Spontaneous labor; however, in the early term period is associated with subsequent sPTB. Further investigation among early term deliveries is warranted to evaluate the risk of sPTB and target interventions in this cohort.